Plantão psicoeducativo: um olhar fenomenológico - Melo Netto, Cícero Bezerra (2014)
This study aimed to understand, according to the reference of existential phenomenology, the foundations of psychoeducational duty: as shown your practice and what kind of contributions have brought to the psychoeducational practice. Specific objectives were intended to understand the basic characteristics of psychoeducational duty and practice that inspired it: the psychological duty, moreover, recognize the unique perspective of psychoeducational duty by reference to some of the notions of existential phenomenology. The research methodology used was the type of documentary analysis: 17 in all academic work were studied, ten studies on psychological duty and seven works on psychoeducational duty, the latter being performed by students of Postgraduate Study Programme in Education: Psychology Education of PUC São Paulo, linked to the Research Group on educational Practices and Psychoeducational Attention to Family, School and Community (ECOFAM). The analysis of the work was divided into two thematic topics for the appointment of the main features observed in each study: Topic 1 (constitutive aspects of the psychological duty) and topical 2 (constitutive aspects of psychoeducational duty). In the latter, we tried, beyond to exposure of the main observations of each author on the subject of psychoeducational duty, articulate, when checked, the similarities between the psychoeducational and psychological duty. Finally, we tried to emphasize the peculiarities of psychoeducational duty with the unique practice in education using the notions of existential phenomenology. The final analyzes suggest the possibility of psychoeducational duty as solicitous care and willingness to listen, conversation and reflection as modes of language that favor and take into account its commitment to education with care to be in diverse educational environments